Implementation of Marketing Mix at The Rinra Makassar Hotel - Adveni, Lusia Vreyda; Muhammad Rafli Mansyur (International Journal of Travel, Hospitality and Events, 2024)
Purpose: The rapid growth of the hotel business in Makassar so that the level of competition between hotels is high. The Rinra Makassar hotel management does this to increase customer interest to compete with other hotels. This study aims to determine the application of the marketing mix in attracting customers at The Rinra Makassar Hotel. Research methods: This study used a descriptive qualitative method. Data collection techniques were observation, interviews, and documentation. The number of informants in this study was as many as two: the Marketing Communication Manager and the Sales Manager. Results and discussion: The Rinra Makassar Hotel employs a comprehensive marketing mix, including advertising, sales promotion, public relations, personal selling, and direct marketing. This integrated approach ensures consistent and impactful communication to add customer value and enhance competitive responses. Implication: The research results on applying the marketing mix carried out by The Rinra Makassar Hotel using the Promotional Mix, namely Sales Promotion Advertising, Public Relations, Personal Selling, and Direct Marketing. Obstacles encountered at The Rinra Makassar Hotel when implementing the promotional mix include promotional activities with the media, price comparisons with other hotels, and personal selling activities.   Keywords: Communication, Marketing, Hotel